2021
DOI: 10.1038/s41591-021-01576-3
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone modulates immature neutrophils and interferon programming in severe COVID-19

Abstract: Although critical for host defense, innate immune cells are also pathologic drivers of acute respiratory distress syndrome (ARDS). Innate immune dynamics during Coronavirus Disease 2019 (COVID-19) ARDS, compared to ARDS from other respiratory pathogens, is unclear. Moreover, mechanisms underlying the beneficial effects of dexamethasone during severe COVID-19 remain elusive. Using single-cell RNA sequencing and plasma proteomics, we discovered that, compared to bacterial ARDS, COVID-19 was associated with expan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 82 publications
(108 reference statements)
12
150
2
1
Order By: Relevance
“…Second, our observations are limited to a single center study, hence further prospective multi-center studies with larger patient samples specifically looking at the correlation between elevated levels of certain cytokines as well as the potential beneficial role of corticosteroid treatment and the risk for developing bacterial superinfections are required to elaborate and verify the observations from our study. Third, in a recent study it was shown that dexamethasone treatment in COVID-19 patients affected circulating neutrophils, altered their IFN signaling and expanded immature neutrophils [87]. Similarly, increase in abnormal/immature neutrophils in the blood stream during severe COVID-19 has been observed by previous studies [20,22,27,53].…”
Section: Plos Pathogensmentioning
confidence: 58%
See 1 more Smart Citation
“…Second, our observations are limited to a single center study, hence further prospective multi-center studies with larger patient samples specifically looking at the correlation between elevated levels of certain cytokines as well as the potential beneficial role of corticosteroid treatment and the risk for developing bacterial superinfections are required to elaborate and verify the observations from our study. Third, in a recent study it was shown that dexamethasone treatment in COVID-19 patients affected circulating neutrophils, altered their IFN signaling and expanded immature neutrophils [87]. Similarly, increase in abnormal/immature neutrophils in the blood stream during severe COVID-19 has been observed by previous studies [20,22,27,53].…”
Section: Plos Pathogensmentioning
confidence: 58%
“…Even though corticosteroid treatment was widely used during previous viral pandemics, such as influenza [76][77][78], SARS-CoV [79,80] and MERS-CoV [81], its use remains controversial [82], since observational studies reported increased mortality and nosocomial infections during influenza [83,84], and delayed clearance of SARS-CoV and MERS-CoV [85,86]. So far, only a limited number of published studies on the mechanistic effects of corticosteroid therapy in COVID-19 is available [87]. However, a few studies reported improved clinical symptoms and oxygenation, reduced length of hospitalization and ICU stay as well as lower 28-day mortality among patients with invasive mechanical ventilation [6,32,40,[88][89][90].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Increased pro-inflammatory cytokines [1][2][3][4] , deficient type I interferon (IFN) responses [5][6][7] , activation of inflammasomes 8 , neutrophils [9][10][11] , and monocytes/macrophages 1,2,[11][12][13][14] have all been associated with severe COVID-19. Coordinated activation of CD8 and CD4 T cells, T cell activation state, and antigen (Ag)-specificity have all been linked to favorable outcomes of SARS-CoV-2 infection [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Females, on the other hand, "had a considerably more tempered neutrophil interferon response, therefore dexamethasone had less impact." Dexamethasone showed different effects according to sex, which could have serious consequences for sex-dependent outcomes and treatment efficacy in severe COVID-19 symptoms [5].…”
Section: Main Bodymentioning
confidence: 99%